Problematika Pendidikan Agama Islam Pada Perguruan Tinggi Agama Islam Di Era Society 5.0 - Istiqomah Istiqomah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Pendidikan agama Islam di Perguruan Tinggi Keagamaan Islam (PTAI), especially at IAI Agus Salim Metro Lampung, faces significant challenges and obstacles in integrating itself with the Society 5.0 era. In the midst of this social revolution, technological constraints, limited internet access, and the lack of technological skills among teachers are the primary issues. Society 5.0 demands large-scale integration of information technology, such as the Internet of Things (IoT) and artificial intelligence, to enhance human life. These constraints include the lack of teacher competency in technology, limitations in technological facilities and infrastructure, and the need for the development of human resources potential (HRP) for both students and lecturers. The research method employs a qualitative descriptive approach with a case study at IAI Agus Salim Metro Lampung. Data were collected through observations, interviews, and documentary research over 30 days. The results indicate that the main challenges involve the limited technological capabilities of teachers, technological infrastructure limitations, and the need for human resource potential development. Obstacles include the limited use of technology media and inadequate teaching methods. Proposed solutions include curriculum updates, technology training for teachers, and the enhancement of technological facilities. A profound understanding of these issues is key to ensuring the relevance and effectiveness of Islamic religious education in the Society 5.0 era.